Hamster (Cricetinae) Motion Assisted by Video Tracker Application on Motion Materials in Junior High School - Sariyah Sariyah; Heru Kuswanto; Heru Nurcahyo; Arina Zaida Ilma; Adha Hujatulatif (Postgraduate, University of Mataram, 2022)
This study aims to explain the phenomenon of motion in hamsters moving in a rolling wheel. Motion is one of the materials taught at the 7th-grade junior high school. The study can be used in learning with the practicum method, namely animal motion. Hamster (Cricetinae) motion is analyzed using a video tracker analysis application with a javascript program. This study used a direct experiment using a hamster using four reference points, namely the forelegs, head, middle body, and hind legs. The results of data analysis from the tracker application were processed using the Microsoft Excel program to obtain a graph of changes in the position and velocity of the hamster. Hamster motion on the rolling wheel is a type of translational motion, namely uniform linear motion.Â Changes in the hamster's position indicate motion on a horizontal line. The velocity obtained in the tracker application is more accurate than manual calculations.